Targeted therapy of non-small cell lung cancer: mechanisms and clinical trials - Yu, Le; Yang, Ruoyi; Long, Zeng; Tao, Qingxiu (Frontiers in Oncology, 2024)
Lung cancer is a leading cause of cancer-related deaths globally, and traditional chemotherapy has limited efficacy in treating advanced non-small cell lung cancer (NSCLC). In recent years, the prognosis for patients with NSCLC has significantly improved due to the development of new treatment modalities, including targeted therapies. Targeted therapies utilize monoclonal antibodies (mAbs), antibody-drug conjugates (ADCs), or small molecule tyrosine kinase inhibitors (TKIs) directed against specific mutated genes such as EGFR and ALK. The development of these drugs has deepened our understanding of NSCLC and improved treatment outcomes for patients. This review aims to summarize the mechanisms and current status of targeted therapy for NSCLC, discuss strategies to overcome acquired resistance, and address current challenges in the field.